Phytoplankton community in the Anthropocene : effects of climate change and eutrophication. - Moresco, Geovani Arnhold (2021)
In the era of the Anthropocene, the effects of climate change on the freshwater ecosystems are clearly complex, since warming and different temperature related drivers influence interacting physical, biogeochemical and biological processes. Climate change is predicted to have huge impacts on the Earth’s ecosystems through temperature increase, changed patterns of precipitation, more frequent extreme weather events, and combinations of these thus, climate change may become one of the major drivers affecting the diversity, composition, structure, and functioning of ecological communities over the next several decades. In this thesis, composed of two papers, we evaluate the effects of multiple factors related to climate change on the natural phytoplankton community. In the first one, we conducted an indoor experiment to test how increasing temperatures influence natural phytoplankton diversity and CO2 emissions in eutrophic ecosystems. Our results experimentally show that, under future scenarios of climate warming, the phytoplankton community composition can respond strongly, affecting ecosystem functions such as biomass production, resource use efficiency, carbon flux balance. Warming clearly aggravated the negative effects of eutrophication through the enhancement of cyanobacteria, all other factors being equal. Since the suggestion that eutrophication may promote climate change by increasing the release of greenhouse gases from fresh waters, it has been found that eutrophication may interact with warming via a positive feedback to atmospheric CH4 emissions. Here, we also found experimental evidence of a positive feedback between the major eutrophication symptom (cyanobacterial blooms) and warming, via higher CO2 emission rates in cyanobacteria dominated warmer systems, besides other changes in key ecosystem functions. In the second paper, we conducted an indoor short-term experiment to test how the natural phytoplankton community subjected to different temperatures reacted to the stressors of climate change (warming, eutrophication, extremes rainfall events) can affect the ecosystem stability. We find that the phytoplankton communities responds differently to disturbances. The environments with cyanobacterial blooms have benefited and proved to be resilient to the extremes rainfall events. In contrast, environments less stressed by warming have a slower response to the event of extreme rainfall, and that they often do not recover their biomass before the extreme rainfall event. Thus, given the multiple effects of climate change, the most stressed environments have greater ecosystem stability (resilience, resistance, and recovery) when compared to the least stressed. In summary, the findings of this thesis, we have experimental evidence with phytoplankton community, that climate change will profoundly affect ecosystem functions (e.g., biomass production, energy transfer, and carbon cycle). In this sense, we hope to contribute with policies to prevent or mitigate the ecological impacts of climate change.